Assessing the performance of segmented timber shell structures within the South African built environment based on the holistic interplay between regional material, manufacturing and assembly conditions - Van der Hoven, Christo (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2024.